(untitled) (Research, Society and Development, 2021)
The analysis of the gaps involving the discipline of sports nutrition in the 50 best undergraduate courses in Nutrition in Brazil, information disclosed through a ranking by INEP in 2016, culminated in a proposal for an extension course. We can observe that in the national curricular guidelines of the undergraduate course in nutrition, instituted by the National Education Council, the discipline of sports nutrition is not considered as mandatory. This fact allows us to suppose that, although the number of nutritionists is significant in Brazil, there is little performance by professionals in the sports field, as a reflection of a teaching deficiency in this area. In view of this scenario, the extension course created would be a facilitator in the process of training students, allowing the approach of topics related to sports nutrition. The course also aims to discuss current myths involving supplementation, prepare professionals to care for high-performance athletes, individuals who practice physical exercises and the development of students’ critical sense during nutritional assessment.